Pressure and flow properties of cannulae for extracorporeal membrane oxygenation I: return (arterial) cannulae. (April 2019) - Broman, Lars Mikael; Prahl Wittberg, Lisa; Westlund, C Jerker; Gilbers, Martijn; Perry da Câmara, Luisa; Swol, Justyna; Taccone, Fabio S; Malfertheiner, Maximilian V; Di Nardo, Matteo; Vercaemst, Leen; Barrett, Nicholas A; Pappalardo, Federico; et al.
Adequate extracorporeal membrane oxygenation support in the adult requires cannulae permitting blood flows up to 6-8 L/minute. In accordance with Poiseuille's law, flow is proportional to the fourth power of cannula inner diameter and inversely proportional to its length. Poiseuille's law can be applied to obtain the pressure drop of an incompressible, Newtonian fluid (such as water) flowing in a cylindrical tube. However, as blood is a pseudoplastic non-Newtonian fluid, the validity of Poiseuille's law is questionable for prediction of cannula properties in clinical practice. Pressure–flow charts with non-Newtonian fluids, such as blood, are typically not provided by the manufacturers. A standardized laboratory test of return (arterial) cannulae for extracorporeal membrane oxygenation was performed. The aim was to determine pressure–flow data with human whole blood in addition to manufacturers' water tests to facilitate an appropriate choice of cannula for the desired flow range. In total, 14 cannulae from three manufacturers were tested. Data concerning design, characteristics, and performance were graphically presented for each tested cannula. Measured blood flows were in most cases 3-21% lower than those provided by manufacturers. This was most pronounced in the narrow cannulae (15-17 Fr) where the reduction ranged from 27% to 40% at low flows and 5-15% in the upper flow range. These differences were less apparent with increasing cannula diameter. There was a marked disparity between manufacturers. Based on the measured results, testing of cannulae including whole blood flows in a standardized bench test would be recommended.